FIRST RECORD OF Carapus bermudenis (JONES, 1874) (ACTINOPTERYGII: CARAPIDAE) IN THE COAST OF BAHIA STATE, NORTHEASTERN BRAZIL (WESTERN ATLANTIC OCEAN) - Lopes, Paulo Roberto Duarte; de Oliveira-Silva, Jailza Tavares; Barreto, Aline Ferreira; Oliveira, Ana Paula Silva (Revista Biociências, 2008)
The first occurrence of Carapus bermudensis (Jones, 1874) (Actinopterygii: Ophidiiformes: Carapidae) in the littoral of Bahia state (Northeastern of Brazil, Western Atlantic Ocean) is presented. This record is based in one specimen measuring 139,0 mm of total length collected still alived in Berlinque’s beach (south of Itaparica Island, about of 13°05’18”S - 38°45’12”W) during low tide. Coloration coincide with diagnosis available to specimens of similar size and small diferences were observed in body proportions which are attributed to intra-especific variation of C. bermudensis along the area of geographic distribution.